2010
DOI: 10.1002/cphc.201000322
|View full text |Cite
|
Sign up to set email alerts
|

Reactivity of Gold Nanobelts with Unique {110} Facets

Abstract: Gold nanobelts were synthesized by directional solidification of the Fe-Au eutectoid followed by selective phase dissolution. Cleaning from organic molecules was performed in alkaline solution by PbO(2) deposition/dissolution to avoid surface reconstruction. The electrochemical behaviour of the Au nanobelts was determined by structure-sensitive electrochemical reactions, and the findings confirm the results obtained by selected area electron diffraction (SAED). The underpotential deposition (UPD) of lead under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
42
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(45 citation statements)
references
References 46 publications
3
42
0
Order By: Relevance
“…However, the benefit of gold as electrocatalyst is that no poisoning intermediates are formed [16,17]. Recently, it was found that gold in the form of nano-sized particles exhibits an unusually high electrocatalytic activity [12,13,16,[18][19][20][21][22][23]. Initial results showed that gold could be a promising candidate for some applications, such as electrocatalytic oxidation of methanol and glucose [18,24].…”
Section: Introductionmentioning
confidence: 98%
See 4 more Smart Citations
“…However, the benefit of gold as electrocatalyst is that no poisoning intermediates are formed [16,17]. Recently, it was found that gold in the form of nano-sized particles exhibits an unusually high electrocatalytic activity [12,13,16,[18][19][20][21][22][23]. Initial results showed that gold could be a promising candidate for some applications, such as electrocatalytic oxidation of methanol and glucose [18,24].…”
Section: Introductionmentioning
confidence: 98%
“…For example, the synthesis of gold nanoflowers and their applications in methanol oxidation and oxygen reduction reactions was reported [22]. Furthermore, the synthesis of Au nanobelts with either {111} or {110} surfaces and their applications in methanol oxidation was described [13,18,25].…”
Section: Introductionmentioning
confidence: 98%
See 3 more Smart Citations